Advances of paeoniflorin in depression: the molecular mechanism and formula application - Hou, Yi; Li, Hong; Zhu, Luochen; Quan, Tian; Feng, Xianhu; Li, Yue; Bian, Yuan; Wei, Yuxun (Frontiers in Pharmacology, 2025)
Paeoniflorin (PF) is widely present in species of the Paeonia genus. In recent years, numerous preclinical studies have shown that PF has preventive and therapeutic effects on various neurological diseases, particularly in the prevention and treatment of depression. Additionally, some classic traditional Chinese medicine formulas containing PF, such as Xiaoyao San, Chaihu Shugan San, and Sini San, have been proven to significantly improve depressive symptoms. However, the antidepressant mechanisms of PF and its containing classic traditional Chinese medicine formulas are not yet fully understood. PF, as a natural glycoside metabolite with a wide margin of safety and good tolerance, exhibits certain toxicity at high concentrations. The differences in standardized methods between the traditional formulations, such as extraction processes, dosages, and inherent metabolite variability in formulations, may affect the interpretation of results and clinical applications. Therefore, this article reviews the antidepressant mechanisms of PF from the perspectives of inhibiting the hypothalamic-pituitary-adrenal axis, increasing the levels of monoamine neurotransmitters, suppressing oxidative stress and apoptosis, regulating calcium homeostasis, inhibiting neuroinflammation, modulating mitochondrial function, regulating cellular autophagy, and increasing the levels of brain-derived neurotrophic factor, and elucidates the antidepressant effects and mechanisms of traditional Chinese medicine formulations containing PF. Additionally, we describe the physicochemical properties, toxinology, pharmacokinetic characteristics, and the transformation of PF in vivo. This review may contribute to the application of PF and its formulations in depression.